INTEGRATED LANDSCAPES IN POLICY, PRACTICE AND EVERYDAY LIFE (ROUTLEDGE, 2025)
Exploring the ways in which an integrated landscape vision can help deliver regional, national, and international agendas, this book investigates how a new idea of landscape can reimagine governance, policy, economics, culture, identity, health, transport, and development priorities by connecting in a more powerful and meaningful way with local aspirations and demands. Developed in fieldwork undertaken over the last decade, the capacity of a landscape-led approach to deal with problems such as rapid urbanisation, water and food security, climate change, air pollution, and health is both timely and topical. Divided into three main sections, it includes illustrated case studies from the UK, Europe, East Asia, South Asia, and more. As part of a strategy to capture, build, and disseminate expertise in this approach, the book aims to develop an interdisciplinary body of work that will appeal to academics and professionals, by bringing together a number of contributors who are operating at the cutting edge of landscape-led large-scale transformation. This book is essential for practitioners and academics of landscape architecture, as well as students in the architecture and design fields.
Keywords: Landscape architecture.; Landscape architecture -- Case studies.; elektronické knihy; electronic books